Microcomputer-Based Data Acquisition System for Crop Production - Wan Ismail, Wan Ishak; Yahya, Azmi; Bardaie, Muhamad Zohadie (Universiti Putra Malaysia Press, 2000)
A Microcomputer-based data acquisition system was design and developed at Michigan State University, USA, to conduct field data studies. The system designed for the research carried out used an Apple lIe microcomputer for collecting data on-board the tractor. An A113 Analog to Digital (A/D) convertor was chosen to interface each analog signal to the microcomputer. A commercially available Dj TPM II was employed to display information such as engine speed, ground speed, drive wheel slip, distance travelled and area covered per hour. The frequency output from the radar unit was channelled through a frequency to voltage (FIV) convertor, so that A113 Analog to Digital (A/D) convertor could read it. The fuel consumption was measured using an EMCO pdp-l fuel flow meter attached to the engine fuel line. The draft of the tillage and other drag equipment was determined using strain gauges attached to the drawbar of the tractor. The system was developed to coHeet the draft and fuel requirements for various farm equipments on different kind of soils. Apparently, Universiti Putra Malaysia has purchased the available system on-board the tractor (Autotronic). The system is capable of measuring engine speed, distance travelled, forward speed, fuel consumption, field capacity, wheel slip, horizontal force at drawbar point and draft forces at the 3-point hitch. A 3-point hitch dynamometer was designed and developed to obtain information on tractive characteristics and implement draft characteristics that are typical for Malaysian conditions.